Contexts and reasons for emoji usage of Chinese Singaporean university students - Lai, Priscilla Zi Ga (Nanyang Technological University, 2020)
Past research has largely focused on quantitative data involving the number of emojis used, and of the small proportion studying contexts and reasons of emoji usage, most do not standardise cultural and linguistic backgrounds of participants and platforms used for data collection. This paper aims to control the platform studied and participant backgrounds to investigate the contexts and reasons for emoji usage of Chinese Singaporean university students on Whatsapp. 10 pairs of Chinese Singaporean university students underwent a text-based interview about the reasons and social contexts behind their emoji usage, and submitted screenshots of a section of their Whatsapp conversation for analysis of the textual context. Nine reasons for emoji usage, and six main reasons and seven sub-reasons for emoji avoidance are found. For contexts of emoji usage, conversation topic and relationship and identity of the interlocutor matter, and most participants utilise emojis at the end of a message or alone as a message. These findings lay the foundation for further investigations with larger participant pools and other Singaporean ethnic groups.